Preparation and characterization of konjac glucomannan and ethyl cellulose blend films. (February 2015) - Li, Xing; Jiang, Fatang; Ni, Xuewen; Yan, Wenli; Fang, Yapeng; Corke, Harold; Xiao, Man
Abstract: Konjac glucomannan (KGM)/ethyl cellulose (EC) blend films were prepared at different blend ratios (KGM/EC = 10/0, 9/1, 8/2, 7/3, 6/4, and 0/10, w/w) in the presence of dibutyl sebacate at 25% (w/w) of total solids content. Hydrogen bond interactions between KGM and EC occurred. An ethyl cellulose phase consisting of oval-shaped particles was uniformly embedded in the KGM continuous phase. The maximum values of tensile strength and elongation at break of blend films were respectively 48 MPa and 12.7% when the ratio of KGM and EC was 7/3 (w/w). Compared to KGM film, the moisture resistance, thermal stability, tensile strength, and elongation at break of blend films were increased. In addition, water vapor transmission was decreased, but the oxygen permeability was increased by blending. Applications of the blend film of KGM and EC for food packaging are suggested. Graphical abstract: Highlights: Films based on konjac glucomannan and ethyl cellulose were prepared and characterized. Blend films were composed of the KGM continuous phase with oval-shaped EC particles embedded in films. Increased contents of konjac glucomannan affected film forming properties.